The mastic tree (Pistacia lentiscus L.) leaves as source of BACs : effect of growing location, phenological stage and extraction solvent on phenolic content - Dragović, Sanja, inženjerka bioprocesnog inženjerstva (Array, 2020)
Research background. Mastic tree (Pistacia lentiscus L.) of the Anacardiaceae family is an evergreen shrub from Mediterranean countries where it is used in traditional medicine. Analysis of P. lentiscus leaf, stem, fruit and root extracts showed high concentrations of principal groups of secondary metabolites (flavonoids, phenolic acids and tannins), suggesting the plant possesses great biological potential. Therefore, the aim of this research is to evaluate the impact of environmental parameters and the extraction solvent type on the concentration of phenols in mastic tree leaf extracts grown at four different locations along the Adriatic coast (Barbariga, Lun, Hvar and Vela Luka) during three phenological stages (early flowering, early fruiting and late fruiting).Experimental approach. Since mastic tree plant has phenolic compounds with different structures and chemical properties, ethanolic and methanolic leaf extracts were analysed using high-performance liquid chromatography (HPLC) coupled with UV/Vis PDA detector. Phenolic compounds were identified by comparing the retention times and spectral data with those of standards at 280 and 340 nm.Results and conclusions. In all samples, phenolic acids and flavonol glycosides were quantified, while catechin was quantified only in methanolic extracts. The 5-O-galloylquinic acid was determined as a predominant phenolic compound in all samples followed by monogalloyl glucose, 3,5-di-O-galloylquinic acid, 3,4,5-tri-O-galloylquinic acid and gallic acid, respectively. Myricetin-3-O-rhamnoside was found to be the predominant flavonol glycoside followed by myricetin-3-O-glucoside, myricetin-3-O-glucuronide, quercetin-3-O-rhamnoside and derivative of flavonol glycoside. The mass concentration of these compounds significantly varied during different phenological stages, at different growing locations and used extraction solvents.